Bran Characteristics and Bread‐Baking Quality of Whole Grain Wheat Flour. Issue 4 (23rd July 2014) - Cai, Liming; Choi, Induck; Lee, Choon‐Ki; Park, Kwang‐Keun; Baik, Byung‐Kee
ABSTRACT: Variations in physical and compositional bran characteristics among different sources and classes of wheat and their association with bread‐baking quality of whole grain wheat flour (WWF) were investigated with bran obtained from Quadrumat milling of 12 U.S. wheat varieties and Bühler milling of six Korean wheat varieties. Bran was characterized for composition including protein, fat, ash, dietary fiber, phenolics, and phytate. U.S. soft and club wheat brans were lower in insoluble dietary fiber (IDF) and phytate content (40.7–44.7% and 10.3–17.1 mg of phytate/g of bran, respectively) compared with U.S. hard wheat bran (46.0–51.3% and 16.5–22.2 mg of phytate/g of bran, respectively). Bran of various wheat varieties was blended with a hard red spring wheat flour at a ratio of 1:4 to prepare WWFs for determination of dough properties and bread‐baking quality. WWFs with U.S. hard wheat bran generally exhibited higher dough water absorption and longer dough mixing time, and they produced smaller loaf volume of bread than WWFs of U.S. soft and club wheat bran. WWFs of two U.S. hard wheat varieties (ID3735 and Scarlet) produced much smaller loaves of bread (<573 mL) than those of other U.S. hard wheat varieties (>625 mL). IDF content, phytate content, and water retention capacity of bran exhibited significant relationships with loaf volume of WWF bread, whereas no relationship was observed between protein content of bran and loaf volume of bread. It appears that U.S. soft and club wheat bran, probably owing to relatively low IDF and phytate contents, has smaller negative effects on mixing properties of WWF dough and loaf volume of bread than U.S. hard wheat bran.